The Impact of Green Lifestyle and Service Quality on Goride Electric Usage: The Moderating Role of Price - Tiolina Evi Pardede; Fangky Antoneus Sorongan (Integrated Journal of Business and Economics (IJBE), 2026)
This study aims to analyze the impact of green lifestyle and service quality on usage decisions of GoRide Electric with price as the moderating variable. 200 users of GoRide Electric are chosen as a sample of this study with the purposive sampling technique. The data are gathered using the questionnaire in Likert scale form. PLS- SEM is used as the technique of data analysis using Smart PLS. The findings reveal that green lifestyle has a positive significant impact on the usage decisions of GoRide Electric and service quality has a positive significant impact on the usage decisions of GoRide Electric while price moderates negatively the impact of green lifestyle on usage decisions of GoRide Electric and moderates positively the impact of service quality on usage decisions of GoRide Electric.